Influence of exercise time of day on salivary melatonin responses - Carlson, L. A.; Pobocik, K. M.; Lawrence, M. A.; Brazeau, D. A.; Koch, A. J. (International Journal of Sports Physiology and Performance, 2019)
Background: Sleep deprivation negatively affects cognition, pain, mood, metabolism, and immunity, which can reduce athletic performance. Melatonin facilitates sleepiness and may be affected by the proximity of exercise to sleep. Purpose: To evaluate the influence of exercise time of day on salivary melatonin (s-melatonin) responses. Methods: Twelve regularly exercising men (age 20.75 [0.62] y, height 1.75 [0.04] m, mass 73.63 [10.43] kg, and maximal oxygen consumption 57.72 [6.11] mL/kg/min) participated in a randomized, crossover design. Subjects completed 3 protocols-morning exercise (09:00 h), afternoon exercise (16:00 h), and no exercise (CON)-at least 5 d apart. Exercise sessions consisted of 30 min of steady-state running at 75% of maximal oxygen consumption. Saliva was collected via passive drool at 20:00, 22:00, and 03:00 h following all sessions. Results: Repeated-measures analysis of variance revealed significant time (P = .001) and condition (P = .026) effects for melatonin. Levels of s-melatonin were significantly increased at 03:00 h compared with 20:00 and 22:00 h for all conditions. Post hoc analyses revealed that s-melatonin at 22:00 h was significantly higher after morning exercise (16.5 [7.5] pg/mL) compared with afternoon exercise (13.7 [6.1] pg/mL) sessions (P = .03), whereas neither exercise condition significantly differed from the control (P > .05). Conclusions: It appears that exercising in the afternoon may blunt melatonin secretion compared with morning exercise. If sleep is an issue, morning exercise may be preferable to afternoon exercise.